Optimalisasi Perpustakaan Desa Untuk Meningkatkan Budaya Literasi di Desa Jatiadi, Kabupaten Probolinggo - Mutinda Teguh Widayanto (LPPM Universitas Putera Batam, 2020)
The progress of a nation is determined by the awareness of the people to increase their knowledge. The progress of enhancing the knowledge, besides being determined by formal education will also determined by the culture of literacy of the community. To develop a culture of literacy for all fields of education (schools, families, and communities), The government of Indonesia in 2016 have lounched the National Literacy Movement (GLN). The existence of a village library will greatly support this movement. In Jatiadi, a Village of Probolinggo district already has a library, but its existence is still not representative to be able to encourage the community to use it. Through this Activity, we want to enhance the benefit of the library by optimizing Village Libraries fungtion to encourage the increasing of the literacy culture of community in order the people can get the information and knowledge they need that is useful for improving their quality and standard of living.